Unitarist and Pluralist Approaches: Employees’ Perception of ‎The Impact of Industrial Relations on Organizational Effectiveness in The Pharmaceutical Industry - Sunand , Potula Laxmana; Sirisetti, Suresh (International Journal of Basic and Applied Sciences, 2025)
This paper looks at employees’ views on industrial relations and how they affect the effectiveness of the pharmaceutical industry in the ‎North Coastal Region of Andhra Pradesh. The discipline explores using unitary and pluralist methods to direct relations between employers and workers and how both approaches impact happiness among employees, workplace productivity, and harmony inside organizations. ‎Unitarism, which centres on unity and harmony within an organization, is distinct from pluralism, which accepts that there are many interests and trade unions help handle disputes. A combination of surveys with interviews was used in this research design, involving both em‎ployees, trade union representatives, and managers. The evidence suggests that giving too much importance to the unitary approach can ‎block employee concerns, which could cause them to be unhappy and resist. The results suggest that using both approaches together pro-‎motes stable organizations, better relationships within the team, and better outcomes. The findings indicate that proper industrial relations ‎policies for pharmaceuticals will result in greater workforce motivation and increased productivity. The study advocates a method that supports workers to speak openly, take part in decision-making, and deal with conflicts properly. The information from these findings is useful ‎for both policymakers and industry leaders working to make industrial relations more successful over time‎.